The manifestation of the spiritual, moral ideas in the teachings of khoja ahmad yassawi and sulayman baqirghani - ТURSUNBOYEVICH, URAZMETOV МANGUBEK (The journal of contemporary issues in business and government, 2021)
This article discusses on two prominent scholars of sufism, Khoja Ahmad Yasawi, that is, the “Yassaviya” tariqat and one of its prominent representatives, Suleiman Baqirghani (Hakim ota), such factors as self-control, strengthening the will, self re-education in tasawwuf iare considered.